Reading for the purpose of responding to literature: EFL students' perceptions of e-books. Issue 1 (2nd January 2016) - Chou, I-Chia
Abstract : As electronic books continue to attract attention as a pedagogical tool in language classrooms, the impact that e-books are expected to have on higher education cannot be ignored. Despite the pervasiveness of e-book reading studies in higher education, most studies show that students' reactions to e-books are often negative. However, the effects of using e-books are considered beneficial in extensive reading programs in many first- or second-language classrooms. The different results may be due to different reading purposes. In addition, limited studies have investigated whether students' perceptions of e-books change over time since many of the e-book reading studies used a survey, rather than longitudinal, approach. Thus, this study intended to determine (1) English as a foreign language (EFL) college students' perceptions of e-books when they read for the purpose of responding to literature rather than for the purpose of intensively studying in an academic context; and (2) whether these perceptions change over time as based on a qualitative perspective. Twenty freshmen enrolled in a literature-based course participated in a semester-long e-book reading. The results showed that the students in this study generally valued the intangible nature of e-books. However, the e-book reading experience was still considered unpleasant to most of the participants in this study. This implies that the reading purpose may not have a great influence on students' perception of e-books. Despite the overall negative perceptions of e-books, the students also demonstrated some improved attitudes toward reading e-books for an entire semester. The findings indicate that when students are given time and opportunities to read e-books, they are likely to develop e-book reading habits and strategies. It would be a pity if we gave up providing students e-books merely because of their initial negative attitudes.